2014
DOI: 10.1016/j.tox.2014.02.014
|View full text |Cite
|
Sign up to set email alerts
|

One man's poison is another man's meat: Using azithromycin-induced phospholipidosis to promote ocular surface health

Abstract: Drug-induced phospholipidosis (PLD) is a common adverse effect which has led to the termination of clinical trials for many candidate pharmaceuticals. However, this lipid-inducing effect may be beneficial in the treatment of meibomian gland dysfunction (MGD). MGD is the major cause of dry eye disease (DED), which affects 40 million people in the USA and has no cure. Azithromycin (AZM) is a PLD-inducing antibiotic that is used off-label to treat MGD, and is presumably effective because it suppresses the MGD-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 35 publications
4
62
0
Order By: Relevance
“…19,20) Indeed, topical azithromycin therapy relieved the signs and symptoms of MGD and restored the biophysical properties of meibomian lipids to normal. 5,21) Furthermore, azithromycin topical treatment significantly reduced the number of plugged orifices and ameliorated acinar atrophy in a special diet-induced MGD mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…19,20) Indeed, topical azithromycin therapy relieved the signs and symptoms of MGD and restored the biophysical properties of meibomian lipids to normal. 5,21) Furthermore, azithromycin topical treatment significantly reduced the number of plugged orifices and ameliorated acinar atrophy in a special diet-induced MGD mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…10 The lipid extractions from samples containing equivalent amount of cells were developed on a high-performance thin-layer chromatography (HPTLC) plate (Silica Gel 60; Merck, Darmstadt, Germany). For nonpolar lipid analysis, the plate was developed in benzene:hexane (65:35, vol/vol) alone.…”
Section: Methodsmentioning
confidence: 99%
“…9 This effect is accompanied by an increased lysosome formation, a decreased cell proliferation, and a holocrine-like lipid secretion, which are the major characteristics of HMGEC differentiation. [9][10][11] In addition, we have discovered that insulin-like growth factor-1 (IGF-1) is essential for meibomian gland health and promotes both cell proliferation and lipid accumulation. 12 Given these findings, we hypothesize that the combination of AZM and IGF-1 will promote cell differentiation and lipid accumulation while preserving the normal cell proliferation in HMGECs.…”
mentioning
confidence: 99%
“…The study demonstrated that azithromycin stimulates the accumulation of free cholesterol, neutral lipids and lysosomes-a phenomenon termed 'drug-induced phospholipidosis'. While phospholipidosis is a common adverse effect in many candidate pharmaceuticals, which may even lead to the termination of a clinical trial, other medications that undergo similar phospholipidosis could be potential treatment options for MGD [24].…”
Section: Antibioticsmentioning
confidence: 99%